2019
DOI: 10.3390/agronomy9050232
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi Modulate the Crop Performance and Metabolic Profile of Saffron in Soilless Cultivation

Abstract: Saffron (Crocus sativus L.) is cultivated worldwide. Its stigmas represent the highest-priced spice and contain bioactive compounds beneficial for human health. Saffron cultivation commonly occurs in open field, and spice yield can vary greatly, from 0.15 to 1.5 g m−2, based on several agronomic and climatic factors. In this study, we evaluated saffron cultivation in soilless systems, where plants can benefit from a wealth of nutrients without competition with pathogens or stresses related to nutrient-soil int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 64 publications
2
36
2
Order By: Relevance
“…The studies involving antioxidant capacity values detected by CUPRAC, DPPH, and FRAP assays are limited. Despite this, similar significant increases in phenolics and antioxidant capacity values have been detected in AMF-treated lettuce (Avio et al 2017), Libidibia ferrea (Dos Santos et al 2017), and saffron (Caser et al 2019). They have also been found in KH-treated kale (Abbey et al 2018) and Plectranthus spp.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The studies involving antioxidant capacity values detected by CUPRAC, DPPH, and FRAP assays are limited. Despite this, similar significant increases in phenolics and antioxidant capacity values have been detected in AMF-treated lettuce (Avio et al 2017), Libidibia ferrea (Dos Santos et al 2017), and saffron (Caser et al 2019). They have also been found in KH-treated kale (Abbey et al 2018) and Plectranthus spp.…”
Section: Discussionmentioning
confidence: 54%
“…The AMF as a biotic factor and the KH as an abiotic factor were both applied to Russian olive, and the beneficial effects of both treatments, either singly or combined, on physiological and biochemical parameters were detected in this work. The effects of AMF and humic substances have been well documented separately for their growth promotion ability (Berruti et al 2016;Canellas and Olivares 2014;Caser et al 2019;Ertani et al 2019;Nardi et al 2016;Rouphael et al 2015;Wang et al 2019). Growth is a significant parameter for plants.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the implications of microbial plant biostimulants on improving produce quality, Chandrasekaran et al [61] reported that the inoculation of PGPR strain, Bacillus subtilis CBR05 induced a significant increase in tomato quality in terms of carotenoids profile (β-carotene and lycopene). Finally, Caser et al [62,63] showed that the inoculation of soilless-grown saffron with Rhizophagus intraradices and to a lesser extent with a mixture of R. intraradices and Funneliformis mosseae boosted significantly the synthesis and accumulation of health-promoting molecules such as anthocyanins, polyphenols and vitamin C; antioxidant activity; and important bioactive compounds in saffron, such as crocin II, picrocrocin and quercitrin.…”
Section: The Role Of Non-microbial and Microbial Biostimulants In Impmentioning
confidence: 99%
“…Inoculation of probiotic microorganisms can be used as an alternative in overcoming the scarcity of inorganic fertilizers due to the high price and availability of fertilizers in certain areas. Inoculation Biofertilizers [21] of probiotic microorganisms that are able to dissolve the P element in acid soils can increase the production of agricultural commodities as reported by many researchers [21][22][23][24][25].…”
Section: Probiotics In Aquaculture Animal Husbandry and Agriculturementioning
confidence: 99%
“…Biofertilizers [25] those who take advantage of situations of animal stress in high stocking density, poor nutrition to cause infections, low growth and feed efficiency rates, and even death (Figure 1). Mass fish deaths often occur in Indonesian waters with the greatest frequency and quantity occurring in lake/reservoir waters, followed by rivers and finally in sea/coast waters.…”
Section: R Intraradices and Funneliformis Mosseaementioning
confidence: 99%